Secret Army, secret war Washington's tragic spy operation in North Vietnam - Tourison, Sedgwick D. (Sedgwick Downey) (Naval Institute special warfare series, 1995)
Former Army intelligence officer and Defense Intelligence Agency analyst "Wick" Tourison unravels the tragically flawed and costly operation that according to many analysts helped trigger, the Vietnam War. Some b&w photos. Annotation copyright Book News, Inc. Portland, Or.